Gender Differences in the Migration Process: A Narrative Literature Review - Athina Anastasiadou; Jisu Kim; Ebru Sanlitürk; Helga A. G. de Valk; Emilio Zagheni (Population and Development Review, 2024)
Migration scholars agree that migration is a highly gendered process. While the literature on this topic is increasing, the knowledge produced remains fragmentary and has not been synthesized systematically yet. This literature review aims at summarizing the current findings of quantitative migration research comparing migration patterns between genders and highlighting gaps and patterns in the literature over time. Following a reproducible and systematic approach, 6032 articles have been scanned and 170 were considered for in-depth content analysis. The review of the literature revealed that women have a lower propensity than men to realize their migration aspirations conditional on migration intentions. Moreover, many articles analyzing migration flows by gender do not support the common narrative of a feminization of migration. Finally, evidence from the migration literature supports the assumption that migrant women experience a double burden of discrimination in the destination country labor market based on their gender and their migration status. It becomes apparent that gender-based comparisons between migration outcomes have received the most attention in the literature followed by the comparison of determinants. The stage of the journey received only little attention. This literature review also focuses on the data sources used to produce our knowledge on gender differences in the migration process. Thereby, it stands out that the majority of papers rely on survey data for the analysis. Digital trace data are a promising source for gender-disaggregated data and can potentially complement the scarce aggregate migration data landscape.
Keywords: 300; migration; gender; sex; literature; review; data